Переносные бетатроны; Всесоюзный семинар "Промышленная гамма-дефектоскопия" - Ананьев Л. М. Лев Мартемьянович; Чахлов В. Л. Владимир Лукьянович; Шарашин Я. А.; Штейн М. М.; Ярушкин Ю. П. (1964, 1964)
В фонде НТБ ТПУ отсутствует